Developmental Characteristics of Musical Ability in High School Students - Guo, Xiaohong; Jing, Lingyu (Journal of Educational Research and Policies, 2026)
This study focuses on Chinese high school students and explores the developmental characteristics of musical ability and its influencing factors. The research found that the high school stage is a critical period for the formation and enhancement of musical ability, with students exhibiting multidimensional development in areas such as perceptual aesthetics, skill cognition, emotional expression, and cultural understanding. Musical ability is influenced by various factors, including cognition, emotion, socio-cultural context, educational policies, and teaching practices. Although the “Double Reduction” policy has increased the emphasis on arts education, issues such as a narrow curriculum, lack of creativity, and limited teacher capabilities persist. Gender differences and family cultural capital significantly affect students’ music preferences and learning opportunities, while teachers’ philosophies and curriculum design are crucial for enhancing musical ability. The study suggests establishing a scientific music ability diagnostic system, improving teacher training and curriculum innovation, and promoting the transformation of music education toward a comprehensive literacy-oriented approach, providing theoretical and practical support for high school music education reform.